Footwear making intermediate (3G Elearning FZ LLC, 2016)
"Footwear Making: Intermediate covers numerous diverse practical and visual skills with knowledge of specialized materials and techniques. Footwear can be defined as garments that are worn on the feet. This book will introduce the knowledge and skills for those studying and/or working in footwear industry."--Provided by publisher.